Correction: Shrewsbury, S.B. The Upper Nasal Space: Option for Systemic Drug Delivery, Mucosal Vaccines and "Nose-to-Brain". Pharmaceutics 2023, 15, 1720 - Stephen B. Shrewsbury (MDPI AG, 2024)
In the original publication [...]